AB0611 Mycophenolate mofetil for the treatment of inflammatory myopathy related interstitial lung disease: a systematic review. (15th June 2017) - Lopez, B; Isenberg, DA; Gordon, PA
Abstract : Background: Inflammatory myopathies (IIM) are a heterogeneous group of rare autoimmune rheumatic diseases in which extramuscular manifestations, especially interstitial lung disease (ILD), are common and may occur in the absence of muscle symptoms. ILD has been identified as a marker of poorer prognosis, with sparse, mainly observational evidence, supporting the use of immunosuppressant therapies. Despite the lack of clinical trial evidence, corticosteroids are considered first-line therapy. Cyclophosphamide is frequently used for severe disease and Azathioprine as maintenance therapy. Mycophenolate Mofetil (MMF) has emerged as a promising treatment, encouraged by data published from a randomised controlled trial comparing Cyclophosphamide with MMF in patients with systemic sclerosis and ILD, which showed similar efficacy and better tolerability in the MMF group (1). Objectives: To examine the evidence supporting the use of MMF in patients with IIM associated ILD. Methods: An electronic literature search was performed using the Ovid platform. Population: Adults diagnosed with IIM according to validated criteria (2, 3) or antisynthetase syndrome (defined by the presence of anti-synthetase antibodies), with ILD demonstrated by HRCT or lung biopsy and treated with MMF, with extractable outcomes regarding ILD. Outcomes were recorded as positive (improvement/stabilisation) and negative (deterioration) as defined by the American Thoracic Society consensus guidelines (4). Results: 506 initial citations were identified, with 23 studies included in the review comprising a total of 82 patients. Median follow up was 12 months, median age 55 years. There was sufficient data to apply America Thoracic Society criteria in 37 patients: improvement/stabilisation n=29, deterioration n=8. Although the criteria could not be applied in 45 patients, improvement/stabilisation was reported in 44 with deterioration in one patient. A non-significant trend to better outcomes was observed when MMF was prescribed as first line therapy, in Jo-1 positive patients and non-Usual Interstitial Pneumonia pattern. Mean Prednisolone dose reduced from 40 mg/day to 10.1 mg/day. No significant toxicity was reported. Conclusions: Mycophenolate Mofetil is a promising drug with encouraging results, but randomised controlled clinical trials are needed to prove its efficacy. References: Tashkin DP, Roth MD, Clements PJ, Furst DE, Khanna D, Kleerup EC, et al. Mycophenolate mofetil versus oral cyclophosphamide in scleroderma-related interstitial lung disease (SLS II): a randomised controlled, double-blind, parallel group trial. Lancet Respir Med. 2016;4(9):708–19. Bohan A, Peter JB. Polymyositis and dermatomyositis (first of two parts). N Engl J Med. 1975;292(7):344–7. Sontheimer RD. Would a new name hasten the acceptance of amyopathic dermatomyositis (dermatomyositis siné myositis) as a distinctive subset within the idiopathic inflammatory dermatomyopathies spectrum of clinical illness? J Am Acad Dermatol. 2002;46(4):626–36. American Thoracic Society. Idiopathic pulmonary fibrosis: diagnosis and treatment. International consensus statement. American Thoracic Society (ATS), and the European Respiratory Society (ERS). Am J Respir Crit Care Med. 2000;161(2 Pt 1):646–64. Disclosure of Interest: None declared